Biallelic copy number variations in both upstream \& downstream enhancers of SHOX gene causes mesomelia and clubfoot without short stature - Yilmaz, Bengisu Guner; Abali, Saygin; Akberzade, Azad; Ay, Beril; Tumer, Sait; Dogan, Ozlem Akgun; Nishimura, Gen; Alanay, Yasemin (SPRINGERNATURE, 2023)
55th European-Society-of-Human-Genetics (ESHG) Conference, Vienna, AUSTRIA, JUN 11-14, 2022